The Raw Mixed Conducting Interphase Affords Effective Prelithiation in Working Batteries. Issue 29 (25th May 2022) - Yue, Xin‐Yang; Yao, Yu‐Xing; Zhang, Jing; Li, Zeheng; Yang, Si‐Yu; Li, Xun‐Lu; Yan, Chong; Zhang, Qiang
Abstract: Contact prelithiation is an important strategy to compensate the initial capacity loss of lithium‐ion batteries. However, the dead Li generated from inadequate Li conversion reduces the cycling stability of rechargeable batteries. Herein a mono‐solvent dimethyl carbonate (DMC) electrolyte was employed in contact prelithiation for the first time. We discover that the low‐organic‐content raw electrolyte interphase (REI) induced by this electrolyte on Li source and anode is a mixed ion/electron conductor. Therefore, electron channels can be maintained even when the Li source has been completely wrapped by the DMC‐derived REI. As a result, an outstanding Li source utilization of 92.8 % and a negligible dead Li yield can be realized. This strategy renders batteries with a very high initial Coulombic efficiency (90.0 %) and an excellent capacity retention (94.9 %) over 210 cycles, highlighting the significance of REI for effective contact prelithiation. Abstract : A raw mixed ion/electron conductor interphase is established on the Li source and anode by using a dimethyl carbonate electrolyte, enabling an unimpeded electron channel structure for elevating the Li source utilization and reducing the formation of dead Li.